Implementation and Deployment of the IMS Learning Design Specification - Gilbert Paquette; Olga Marino; Ileana De la Teja; Michel Lonard; Karin Lundgren-Cayrol; Julien Contamines (The Canadian Network for Innovation in Education (CNIE), 2005)
Knowledge management in organizations, the learning objects paradigm, the advent of a new web generation, and the "Semantic Web" are major actual trends that reveal a potential for a renewed distance learning pedagogy. First and foremost is the use of educational modelling languages and instructional engineering methods to help decide how to aggregate learning objects in learning and knowledge management environments. This article proposes a set of tools under implementation, such as a graphic Learning Design Editor and a delivery system, using learning object repositories to create IMS-LD online environments. We also propose a strategy for the deployment of learning design tools and methods in learning organizations.